2020
DOI: 10.3390/jcm9041015
|View full text |Cite
|
Sign up to set email alerts
|

Body Image in Patients with Marfan Syndrome

Abstract: This study aimed to assess body image impairments of individuals with Marfan syndrome and to determine to what extent psychological, physical, and sociodemographic factors influence body image. We assessed the physical fitness and psychosocial health of 42 patients with Marfan syndrome at the beginning of an inpatient rehabilitation program. All participants filled out a body image questionnaire consisting of two scales: (1) Negative Body Evaluation and (2) Vital Body Dynamics. We compared body image data of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Consequently, most patients are closely monitored, with serial cardiovascular assessments from early childhood (2)(3)(4)(5). Additionally, patients with MFS often have to cope with skeletal or ocular abnormalities leading to a characteristic appearance, which is not only subjectively perceived by themselves, but is also visible to others (6,7). Recent studies have indicated that the combination of physiological and psychological symptoms may lead to a decreased quality of life (QOL) in individuals with MFS (3).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most patients are closely monitored, with serial cardiovascular assessments from early childhood (2)(3)(4)(5). Additionally, patients with MFS often have to cope with skeletal or ocular abnormalities leading to a characteristic appearance, which is not only subjectively perceived by themselves, but is also visible to others (6,7). Recent studies have indicated that the combination of physiological and psychological symptoms may lead to a decreased quality of life (QOL) in individuals with MFS (3).…”
Section: Introductionmentioning
confidence: 99%
“…MFS patients often report having a significantly impaired body image, predicted by depression and anxiety (Hansen et al, 2020 ). When comparing operated and non-operated subgroups of MSF patients, it emerged that the operated group reported more alcohol consumption while the non-operated group had more sleep disturbances.…”
Section: A Practical Example From Italy: the Psychological Service Of...mentioning
confidence: 99%